Cultivar and Tree Density As Key Factors in the Long-Term Performance of Super High-Density Olive Orchards - Díez, Concepción M.; Moral, Juan; Cabello, Diego; Morello, Pablo; Rallo, Luis; Barranco, Diego (Frontiers in Plant Science, 2016)
Super high-density (SHD) olive orchards are rapidly expanding since the first plantation was set up in Spain in the 1990s. Because there are no long-term studies characterizing these systems, it is unknown if densities above a certain threshold could trigger competition among fully-grown trees, compromising their development. Over 14 years we have evaluated the performance of the major olive cultivars currently planted in SHD systems (‘Arbequina’, Arbequina IRTA-i·18R, ‘Arbosana’, ‘Fs-17’, and ‘Koroneiki’) and nine SHD designs ranging from 780 to 2254 trees ha-1 for the cultivar ‘Arbequina’. Remarkably, the accumulated fruit and oil production of the five cultivars increased linearly over time. Our data indicated the favorable long-term performance of the evaluated cultivars with an average annual oil production of 2.3 t ha-1. Only ‘Fs-17’ did not perform well to the SHD system in our conditions and it yielded about half (1.2 t ha-1) of the other cultivars. In the density trial for ‘Arbequina’, both fruit and oil accumulated production increased over time as a function of tree density. Thus, the accumulated oil yield ranged from 16.1 t ha-1 for the lowest density (780 trees ha-1) to 29.9 t ha-1 for the highest (2254 trees ha-1). In addition, we note that the accumulated production per surface unit showed a better correlation with the hedgerow length than the tree density. Thus, the current planting designs of SHD olive orchards can be further improved taking this parameter into account. Despite observations that some irregular patterns of crop distribution have arisen, our olive hedgerows are still fully productive after 14 years of planting. This result contradicts previous experiences that showed declines in production seven or eight years after planting due to high vigor, shading, and limited ventilation.